Effects Of Domestic Processing On Quality Of Jering [Pithecellobium Jiringa (L.)] - Sridaran, Ashuwini (2013)
Pithecellobium jiringa L. (jering) is a non-conventional legume commonly consumed by people of the South-East Asia region. This study is specifically concerned with physicochemical, antioxidant, antinutritional and functional properties of jering and effects of domestic processing (hydrothermal and fermentation) on these quality parameters. Jering was subjected to boiling (21.0 ± 1.0 minutes), pressure cooking (121 °C, 0.2 MPa, 20 minutes), yeast (Saccharomyces cerevisiae) and Rhizopus spp. fermentation. Jering had high moisture content (58.55%), crude protein (14.19%), nitrogen free extract (NFE) (82.1%) and gross energy values (1662.49 kJ 100 g-1) and low crude lipid level (1.45%). Rhizopus spp. fermentation improved crude protein and fiber contents. Hydrothermal processing and yeast fermentation increased the NFE and gross energy values. Jering exhibited high amino acid score (AAS) (92-250%) and significant levels (p<0.05) of sulphur containing amino acids (SAA). Rhizopus spp. and yeast fermentation improved amino acid profile and AAS. Fatty acids detected were primarily unsaturated fatty acids (54.73%). Hydrothermal processing and fermentation reduced the polyunsaturated/saturated fatty acids (P/S) ratio. Jering exhibited superior total phenolic content (TPC) and total flavonoids content (TFC). Rhizopus spp. fermentation significantly improved (p<0.05) TPC and TFC. Hydrothermal processing considerably reduced TPC (35-98%) and TFC (61-90%). Yeast fermentation also reduced TPC (74-94%) and TFC (83-94%). Tannin content was the highest in raw jering followed by boiled, pressure cooked and fermented jering.